Comparative outcomes of free flap versus local flap reconstruction in post-traumatic lower limb defects following orthopaedic fixation: a meta-analysis - Suliman, Osman; Almehmadi, Maan; Alraddadi, Danah; Alharbi, Fatimah; Aboufarha, Khaled; Alsaedi, Nesreen; Alharbi, Malak; Alsaedi, Abdullah; Altom, Sara (International Journal Of Community Medicine And Public Health, 2026)
Post-traumatic lower limb defects following orthopedic fixation present significant reconstructive challenges, and the choice between free flap and local flap reconstruction remains critical for limb salvage, functional recovery, and complication prevention. This study systematically evaluated and compared the outcomes of free flap versus local flap reconstruction in the management of post-traumatic lower limb soft-tissue defects after orthopedic fixation. A comprehensive literature search was conducted in PubMed, Scopus, Web of Science, and the Cochrane Library for studies published up to October 2025, including randomized controlled trials, cohort studies, and case series that directly compared free and local flap techniques in adult patients. Data were extracted on flap survival, infection and complication rates, time to bone union, functional outcomes, and the need for re-operation. Twenty-seven studies met the inclusion criteria, demonstrating that free flaps were more reliable for large or complex defects and were associated with lower rates of deep infection and flap failure in high-risk wounds, while local flaps offered shorter operative times and reduced donor-site morbidity but showed higher rates of partial necrosis and limited effectiveness in extensive defects. Functional outcomes and time to fracture union were generally comparable between the two techniques; however, free flaps provided superior results in cases with compromised soft-tissue envelopes. Both free and local flaps are effective reconstructive options following lower limb trauma with orthopedic fixation, with free flaps being preferable for large or highrisk defects and local flaps remaining suitable for smaller, less complex wounds, emphasizing that defect size, vascular status, and patient-specific factors should guide individualized reconstructive decision-making.